Optimal staffing in community health centers to improve quality of care. (8th October 2020) - Luo, Qian; Dor, Avi; Pittman, Patricia
Abstract: Objective: To explore optimal workforce configurations in the production of care quality in community health centers (CHCs), accounting for interactions among occupational categories, as well as contributions to the volume of services. Data Sources: We linked the Uniform Data System from 2014 to 2016 with Internal Revenue Service nonprofit tax return data. The final database contained 3139 center‐year observations from 1178 CHCs. Study Design: We estimated a system of two generalized linear production functions, with quality of care and volume of services as outputs, using the average percent of diabetic patients with controlled A1C level and hypertensive patients with controlled blood pressure as quality measures. To explore the substitutability and complementarity between staffing categories, we estimated a revenue function. Findings: Primary care physicians and advanced practice clinicians achieve similar quality outcomes (3.2 percent and 3.0 percent improvement in chronic condition management per full‐time equivalent (FTE), respectively). Advanced practice clinicians generate less revenue per FTE but are generally less costly to employ. Conclusion: As quality incentives are further integrated into payment systems, CHCs will need to optimize their workforce configuration to improve quality. Given the relative efficiency of advanced practice clinicians in producing quality, further hiring of these professionals is a cost‐effective investment for CHCs.